The Middle East : a political and economic survey - Royal Institute of International Affairs (London : Royal Institute of International Affairs, 1950)
"Much has been written in recent years about the Middle East. At the same time, no other region has been as misunderstood, nor framed in so many cliches and mistakenly-held beliefs." "In this much-needed expose, Fred Halliday selects one hundred of the most commonly misconstrued 'facts' - in the political, cultural, social and historical spheres - and illuminates each case without compromising its underlying complexities. The Israel-Palestine crisis, the Iran-Iraq war, the US-led Gulf incursions, the Afghan-Soviet conflict and other significant milestones in modern Middle Eastern history come under scrutiny here, with conclusions that will surprise and enlighten many for going so persuasively against the grain."--BOOK JACKET.
Includes indexes.
Includes bibliographical references and indexes.
Keywords: Middle East -- Politics and government -- 1979-